IMPACT OF EMPLOYEE TURNOVER ON HOTEL INDUSTRY- A STUDY OF SELECTED HOTELS OF NEW DELHI - Singh, Dilbag; Amandeep (International Journal of Research -GRANTHAALAYAH, 2017)
Hotel industry is a part of Tourism Industry which is flourishing in India than ever before, according to 2017 report of World Economic Forum India has reached the 40th rank in the world from 52 during 2015. This has been result of immense efforts of the Government and the Industry positive steps in boosting its appeal as a tourist and hospitality destination on the globe. There are various International hotel chains already in India which are expanding their room inventory at a fast pace to meet the future demands of accommodation and leisure services. But with every success there comes some kind of problems or concerns which are needed to tackle as they might slowdown the organization or the industry as a whole. One of the major issues which have been part of every growing industry in past is to row out itself from the problem of employee turnover rate. It is said that employee turnover is one silent part of human resource management which can have a negative impact for the organization if managed inadequately. This paper is an attempt to find out the reasons why hotel industry in India is facing this issue and what are the possible effects of it on the industry which might slow or hold still the growth of industry as forecasted.